2012
DOI: 10.1162/jocn_a_00178
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Visual Letter Perception

Abstract: We describe a novel method for tracking the time course of visual identification processes, here applied to the specific case of letter perception. We combine a new behavioral measure of letter identification times with single-letter ERP recordings. Letter identification processes are considered to take place in those time windows in which the behavioral measure and ERPs are correlated. A first significant correlation was found at occipital electrode sites around 100 msec poststimulus onset that most likely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
5
19
0
Order By: Relevance
“…This small time window (i.e., 120 ms) is certainly computationally too short to encompass all of these nonvisual processes, suggesting that visual and nonvisual processes cannot be encapsulated, and have to interact earlier in time (Carreiras et al, 2014). Similarly, the fact that abstract or phonological effects have been reported much earlier than 290-300 ms (e.g., Madec et al, 2012;Petit et al, 2006) also indicates that visual and nonvisual levels of processing are coactivated at some point in time during letter identification, and would therefore interact following a cascaded interactive-activation framework (McClelland & Rumelhart, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This small time window (i.e., 120 ms) is certainly computationally too short to encompass all of these nonvisual processes, suggesting that visual and nonvisual processes cannot be encapsulated, and have to interact earlier in time (Carreiras et al, 2014). Similarly, the fact that abstract or phonological effects have been reported much earlier than 290-300 ms (e.g., Madec et al, 2012;Petit et al, 2006) also indicates that visual and nonvisual levels of processing are coactivated at some point in time during letter identification, and would therefore interact following a cascaded interactive-activation framework (McClelland & Rumelhart, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that visual templates would be processed around 150-170 ms (Rey, Dufau, Massol, & Grainger, 2009), followed by abstract and phonological processing around 220 ms (Petit et al, 2006). Recent evidence has suggested that phonological processes (i.e., access to the letter's name) may start earlierthat is, between 150 and 190 ms-and that letter identification processes would be supported by recurrent interactions between visual and phonological codes until response selection (Madec, Rey, Dufau, Klein, & Grainger, 2012).…”
mentioning
confidence: 99%
“…This result could be explained by assuming that the amount of variance devoted to visual identification processes is not fixed, either, among word categories. Indeed, if these central processes are fast and efficient (as for high-frequency monosyllabic words), then the total amount of the variance in naming could be influenced less by these processes, and the contribution of articulatory factors might therefore be stronger (for a similar result in single-letter naming, see Madec et al, 2012). Conversely, if central processes are slower and more time consuming, then they would account for a larger amount of the total variance, and as a consequence, the amount of variance captured by onset phonemes would decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a recent study using a large database of letternaming and delayed-naming response times, Madec, Rey, Dufau, Klein, and Grainger (2012) found that the delayed-naming times predicted 79 % of the naming time variance. This result suggests that output articulatory processes might be responsible for a much greater percentage of the total item variance than was initially estimated on the basis of the phonetic properties of the initial phoneme (which might, therefore, not capture all of the articulatory-related variance).…”
mentioning
confidence: 97%
See 1 more Smart Citation